Classificação ecodinâmica das unidades de paisagem na área de preservação ambiental das onças, no município de São João do Tigre/PB - Lima, Maria Niedja Silva (2014)
Into a systemic view, landscapes studies seek to integrate the discernible units in the environment, these units being defined as Geosystem, Geofácie and Geótopo, which seek to relate all activities developed in the biotic and abiotic environment, with Man as modifying agent of natural dynamics. The Ecodynamic seeks to combine the processes of environment morphogenesis and pedogenesis to classify them within a Stable Intermediate and Unstable range, considering all the factors that shape the landscape, where it is considered a product of the existing relationships. This study aimed to identify landscape units of Permanent Preservation Area (APA) of Onças, in São João do Tigre, evaluating the processes of vulnerability of the area. It was done fieldworks in order to know the area and identify landscape units previously proposed by Bertrand (1979) and Sotchava (1977). After identification of the rocks, slope, soil, climate and vegetation, dominant elements in the APA, the existing landscape units were identified and classified within the APA Geosystem Serra of the Jaguars, Geofacies Surface Summit Shed and river valley, beyond of Geotopes. The integration of the products generated regarding the rocks, slope, soil, climate and vegetation, allowed an analysis of these factors, then their synthesis, thereby generating a map ecodynamic. Within this map classes were defined stability to instability, showing that much of the APA is an environment equivalent to an Intermediate range, whereas the activities of plant extraction and agricultural exploitation are major triggers of changes in the APA. For the area identified as unstable, it is recommended to use exemption and reforestation. In order to improve the Ecodynamic situation found, it is recommended to replace part of the economic activities developed for ecotourism silvopastoralism in parallel to reforestation.